PENGARUH PERSEPSI ATAS LINGKUNGAN SEKOLAH DAN KEDISIPLINAN TERHADAP PRESTASI BELAJAR BAHASA INGGRIS - Suhendra Suhendra; Supeno Supeno (Universitas Indraprasta PGRI, 2020)
The purpose of this study was to determine the effects of perceptions of school environment and discipline jointly towards English learning achievement, the effect of perceptions of school environment towards English learning achievement, the effect of discipline towards English learning achievement at Private Vocational High Schools in Kabupaten Tangerang. The research method used in this study is the survey method. Sample of 47 students was selected randomly from all private vocational students in Kabupaten Tangerang. Based on data analysis, it can be concluded that: 1) The results of the first hypothesis testing concluded that there was a significant effect of perception of school environment and discipline jointly towards English learning achievement at private vocational high schools in Kabupaten Tangerang. This is proved by the value of sig. 0,000 <0.05 and Fh = 35,702. 2) The results of the second hypothesis testing concluded that there was a significant effect of perceptions of school environment towards English learning achievement at private vocational high school in Kabupaten Tangerang. This is proved by the value of Sig. 0,000 <0.05 and th = 5,750. 3) The results of the third hypothesis testing concluded there was a significant effect of discipline towards English learning achievement at private vocational high schools in Kabupaten Tangerang. This is proved by the value of Sig. 0,000 <0.05 and th = 4,901.